The Role of Risk Management in Banking - Tiara Putri Agustina; Arivatu Ni’mati Rahmatika (INCOME: Innovation of Economics and Management, 2022)
The banking industry is an industry that is full of risks, especially because it concerns the management of people's money and is filtered in the form of investment. This article uses literature study research. To minimize the risks faced, bank management must have adequate expertise and competence, so that various risks that have the potential to arise can be anticipated from the beginning, and seen for better handling. The types of risks presented by economists are very diverse but substantially similar to each other. Broadly speaking, the grouping of risks carried out by economists is almost the same description and scope. The larger and more modern banks, the more and more complex the risks they face. Financial risks faced by the banking industry can be broadly grouped into 5 (five) major risks, namely: (1) credit risk, (2) market risk, (3) liquidity risk, (4) operational risk, and (5) capital risk. These risks are presented in financial ratios, which indicate that: the performance that management achieves in managing the bank.